A Targeted Next-Generation Sequencing Assay Detects a High Frequency of Therapeutically Targetable Alterations in Primary and Metastatic Breast Cancers: Implications for Clinical Practice. (7th April 2014) - Vasan, Neil; Yelensky, Roman; Wang, Kai; Moulder, Stacy; Dzimitrowicz, Hannah; Avritscher, Rony; Wang, Baliang; Wu, Yun; Cronin, Maureen T.; Palmer, Gary; Symmans, W. Fraser; Miller, Vincent A.; et al.
Abstract: Background: The aim of this study was to assess the frequency of potentially actionable genomic alterations in breast cancer that could be targeted with approved agents or investigational drugs in clinical trials using a next-generation sequencing-based genomic profiling assay performed in a Clinical Laboratory Improvement Amendments-certified and College of American Pathologists-accredited commercial laboratory. Methods: Fifty-one breast cancers were analyzed, including primary tumor biopsies of 33 stage I–II and 18 stage IV cancers (13 soft tissue, 3 liver, and 2 bone metastases). We assessed 3, 230 exons in 182 cancer-related genes and 37 introns in 14 genes often rearranged in cancer for base substitutions, indels, copy number alterations, and gene fusions. The average median sequencing depth was 1, 154×. Results: We observed 158 genomic alterations in 55 genes in 48 of 51 (94%) tumors (mean 3.1, range 0–9). The average number of potentially therapeutically relevant alterations was similar in primary (1.6, range 0–4) and in heavily pretreated metastatic cancers (2.0, range 0–4) ( p = .24). The most common actionable alterations were in PIK3CA ( n = 9, phosphatidylinositol 3-kinase [PI3K]/mammalian target of rapamycin [mTOR] inhibitors), NF1 ( n = 7, PI3K/mTOR/mitogen-activated protein kinase inhibitors), v-akt murine thymoma viral oncogene homolog 1-3 ( n = 7, PI3K/mTOR/AKT inhibitors), BRCA1/2 ( n = 6, poly[ADP-ribose] polymerase inhibitors), and CCND1, 2 and CCNE ( n = 8)/cycline dependent kinase (CDK)6 ( n = 1) (CDK4/6 inhibitors), KIT ( n = 1, imatinib/sunitinib), ALK ( n = 1, crizotinib), FGFR1, 2 ( n = 5, fibroblast growth factor receptor inhibitors), and EGFR ( n = 2, epidermal growth factor receptor inhibitors). Our sequencing assay also correctly identified all six cases with HER2 ( ERBB2 ) amplification by fluorescence in situ hybridization when tumor content was adequate. In addition, two known activating HER2 mutations were identified, both in unamplified cases. Conclusion: Overall, 84% of cancers harbored at least one genomic alteration linked to potential treatment options. Systematic evaluation of the predictive value of these genomic alterations is critically important for further progress in this field. Abstract : The aim of this study was to assess the frequency of potentially actionable genomic alterations in breast cancer that could be targeted with approved agents or investigational drugs in clinical trials using a next-generation sequencing-based genomic profiling assay. Systematic evaluation of the predictive value of these genomic alterations is critically important for further progress in this field.